2016
DOI: 10.1016/j.brainres.2016.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed ultrasound expands the extracellular and perivascular spaces of the brain

Abstract: Diffusion within the extracellular and perivascular spaces of the brain plays an important role in biological processes, therapeutic delivery, and clearance mechanisms within the central nervous system. Recently, ultrasound has been used to enhance the dispersion of locally administered molecules and particles within the brain, but ultrasound-mediated effects on the brain parenchyma remain poorly understood. We combined an electron microscopy-based ultrastructural analysis with high-resolution tracking of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
(74 reference statements)
5
22
0
Order By: Relevance
“…ZsGreen expression was never observed in the contralateral striatum. Broadly speaking, these findings are in agreement with previous studies on the influence of ultrasound on therapeutic penetration in brain tissue …”
supporting
confidence: 93%
See 1 more Smart Citation
“…ZsGreen expression was never observed in the contralateral striatum. Broadly speaking, these findings are in agreement with previous studies on the influence of ultrasound on therapeutic penetration in brain tissue …”
supporting
confidence: 93%
“…In addition to its ability to enable the delivery of therapeutic agents across the BBB, FUS also enhances the dispersion of therapeutic agents through brain tissue . However, this secondary effect has yet to be leveraged therapeutically.…”
mentioning
confidence: 99%
“…Thus, these were measures essentially of advection without any confounding factors and showed the same distribution so that a “retardation factor” (see Introduction) was not called for, even for the nanoparticle! (Other researchers have shown benefits from pre-expanding the interstitium for large particles such as viruses [ 33 ].) We may conclude that molecular size does not significantly impact distribution due to advection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study corroborates these findings and provides evidence that FUS contributes to enhanced interstitial convective transport in solid tumors, in addition to alleviating vascular barriers. In addition to these mechanisms, recent work suggested that FUS can expand the extracellular and perivascular spaces (58). Whereas this is a very important work in the field, studies were performed in healthy ex vivo rat brain slices.…”
Section: Discussionmentioning
confidence: 99%